PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DENGAN MEDIA PERMAINAN KARTU DESTINASI UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SEJARAH SISWA KELAS X IIS 2 SMA NEGERI 5 SURAKARTA PADA SEMESTER GENAP TAHUN AJARAN 2015/2016 - Fadhilla, Hidayatul; Bachri, Saiful; Djono, Djono (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2017)
The purpose underlying this study is to increase interest and learning outcomes of students of X IIS 2 SMAN 5 Surakarta by implementing Cooperative learning method type Teams Games Tournaments (TGT) with Destination Card Game in history subject. This research is a Classroom Action Research (CAR). The research conducts in two cycles, with each cycle consisting of a plan of action, action, observation, and reflection. The subjects are students of X IIS 2 SMAN 5 Surakarta which is consisting 27 people. Source of data from the teachers, the students, the learning process, and the documents. Data collection technique is conducted by interviewing, observing, testing, giving questionnaires and document analyzing. The researcher uses triangulation of data and triangulation methods to examine the validity of the data. Interactive analysis and comparative descriptive analysis are used to analyzing the data. The research model includes the Spiral Model (Planning, Acting, Observing and Reflecting). The result shows that the teacher?s and students? activities in learning process can be categorized as good which means the learning process in History class goes well. The outcomes of learning activities in precycle is 60.81% increases to 74.77% in the first cycle and increases to 87.00% in the second cycle. The implementation of cooperative learning method with the type of Teams Games Tournament (TGT) by using Destination Card Game has increased the interest and the learning outcomes of students of Social 2 grade X of precycle to the first cycle and from the first cycle to the second cycle. The learning interest of precycle is 60.95% increase to 76.03% in the first cycle and increase to 83.02% in the second cycle. The completeness of student learning outcomes in precycle amount to 51.85% increase to 74.07% in the first cycle and successfully increase in the second cycle into 88.89%. Based on the research finding and discussion, it can be concluded that Cooperative Learning method with the type of Teams Games Tournament (TGT) by using Destination Card game can increase the interest and learning outcomes of students of X IIS 2 SMAN 5 Surakarta.